2015
DOI: 10.1007/s10853-015-9230-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of electromigration damage in SAC305 solder joints by adding Ni nanoparticles through flux doping

Abstract: The characteristics of interfacial intermetallic compounds (IMCs) can have serious impact on the reliability of solder joints. In this study, Ni nanoparticles (NPs) were added to SAC305 solder/Cu substrate interface by flux mixing. The effects of Ni NP addition on electromigration (EM) under high current density were investigated. EM tests with a maximum duration of 1128 h were conducted under a current density of 1 9 10 4 A/cm 2 , at 80 ± 3°C on the solders prepared using 0 and 2 wt% Ni NPs-doped flux. At 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 35 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…A large number of research and review papers described the impact of dopants on the microstructure and physical properties of SAC solders in the liquid and/or solid state [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It was shown that minor insertions of additional elements modify the microstructure and improve different properties of SAC alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of research and review papers described the impact of dopants on the microstructure and physical properties of SAC solders in the liquid and/or solid state [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It was shown that minor insertions of additional elements modify the microstructure and improve different properties of SAC alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the authors of Refs. [6,[9][10][11] pointed out that additional Co, Ni or Zn atoms substituted Cu atoms in the Cu 6 Sn 5 phase and suppressed the formation of the brittle Ag 3 Sn phase. Such structural changes improve both the microstructure and the mechanical properties such as microhardness and shear strength of doped SAC solders and their joints.…”
Section: Introductionmentioning
confidence: 99%
“…[18,[20][21][22][23] However, to the best of our knowledge, there are no literature data related to the structure and thermophysical properties of nanocomposite SAC solders with nano Ni additions in the liquid state after melting. In this work, we carried out investigations of the electrical conductivity of nanocomposite SAC in the liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…The study related to the reliability of Cu/Al bond in comparison with that of Au/Al bond at comparable temperature is presented in [8,9]. Research related to the effects of Ni nanoparticles addition on EM under high current density was studied in [10], where authors presented reduction approach of the EM damage in SAC305 (lead free solder SN96) solder joints in order to ensure more reliable solder joints.…”
Section: Introductionmentioning
confidence: 99%